Biomechanics—Hot Topics Part I. (March 2018) - Bottlang, Michael; Lorich, Dean G.; Dvorzhinskiy, Aleksey; Gausden, Elizabeth; Slobogean, Gerard P.; Schemitsch, Geoffrey W.; Sanders, David W.; Schemitsch, Emil H.
Abstract : Summary: This study summarizes presentations of a symposium on biomechanically related hot topics of the 2015 Basic Science Focus Forum. Each topic emphasizes a biomechanical challenge common to all 4 of these presentations: an ideal fixation technique should deliver ample stability and sufficient flexibility to prevent fixation failure and to restore normal function.